Utilization of pineapple peels in the production of probiotic Tepache for immune enhancement among members of Majelis Taklim Nurul Muhajirin in Makassar - Hilda Karim; Oslan Jumadi; Hartati Hartati; Andi Faridah Arsal; A. Irma Suryani (Jurnal Hasil Inovasi Masyarakat, 2024)
This training aimed to empower the members of Majelis Taklim Nurul Muhajirin in Tamalate District, Makassar City, by educating them on the use of pineapple peels to produce probiotic Tepache. Tepache is a traditional Mexican fermented beverage made from pineapple peels, sweetened with brown sugar, and flavored with cinnamon and cloves. This drink contains probiotics that benefit both immunity and digestive health. Prior to the training, the members of Majelis Taklim had never received such training and were unfamiliar with how to utilize pineapple peels as an ingredient for a healthy drink. Through a hands-on demonstration, participants learned how to make Tepache and took part in an organoleptic test to assess the drink's taste and quality. The training results showed high enthusiasm from the participants, who were pleased to learn that pineapple peels, which they previously considered waste, could be turned into a refreshing and healthy beverage. This training is expected to raise awareness and improve the members’ ability to productively utilize fruit waste.